Research Trends on Mathematics Education of Multicultural Students in Turkey - Feyyaz Öztop (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Examining the research on mathematics education of multicultural students in Turkey and identifying weak points can be a guide for better educational practices. The purpose of this study was to review previous studies on the mathematics education of students from different cultures in Turkey and to identify trends in those studies. The research was conducted using the document analysis method. The research data was collected from 36 studies that were found after scans in the Google Scholar and CoHE Thesis Center. Content analysis was used for analyzing the acquired data. The results show that 2022 included the most research on the topic, with secondary school students preferred as research participants in the greatest numbers. Additionally, it has been found that there were significantly more studies out there that purpose to describe the topic. On the other hand, it was determined that the most focused topic in the studies was the challenges in teaching and learning mathematics. It is recommended that more research be conducted on the mathematics education of primary school students from different cultures in Turkey.